Between Islam and the Sacred Forest - Gruber, Martin; Seidel, Frank (Journal of Anthropological Films, 2017)
An anthropologist and a linguist from Germany are trying to understand a ritual, taking place in a small village on the coast of Guinea, West Africa. They are told that two seemingly conflicting ceremonies take place during a four-day event commemorating a recently deceased woman: A Muslim celebration of the 40th day after death conducted by a local Imam and the Mkisaata ritual, performed by the members of a Nalu female secret society in honour of its deceased member. As the involved men explain the filmmakers their respective version of the events, the researchers get increasingly drawn into the ritual by the women of the secret society and become part of their performance. “Between Islam and the Sacred Forest“ tells a story about the womens' power to create their own space in a male dominated society. At the same time it deals with the possibilities and impossibilities of audio-visual ethnography.